Existence of positive solutions for some nonlinear elliptic problems in unbounded domains of ℝn - Noureddine Zeddini (Abstract and Applied Analysis)
This paper deals with a class of nonlinear elliptic equations in an unbounded domain D of ℝn, n≥3, with a nonempty compact boundary, where the nonlinear term satisfies some appropriate conditions related to a certain Kato class K∞(D). Our purpose is to give some existence results and asymptotic behaviour for positive solutions by using the Green function approach and the Schauder fixed point theorem.